Durable Response in Patients With Refractory Fistulizing Perianal Crohn's Disease Using Autologous Mesenchymal Stem Cells on a Dissolvable Matrix: Results from the Phase I Stem Cell on Matrix Plug Trial. Issue 2 (21st November 2022) - Dozois, Eric J.; Lightner, Amy L.; Dietz, Allan B.; Fletcher, Joel G.; Lee, Yong S.; Friton, Jessica J.; Faubion, William A.
Abstract : BACKGROUND: Refractory perianal Crohn's disease remains notoriously difficult to treat. We developed a novel technology using a commercially available bioabsorbable fistula plug to deliver autologous adipose-derived mesenchymal stem cells. OBJECTIVE: This study aimed to assess therapeutic safety and feasibility in the completed STOMP (stem cells on matrix plugs) phase 1 clinical trial. DESIGN: Prospective single-arm phase I clinical trial. SETTING: Tertiary academic medical center. PATIENTS: Adults (aged 18–65 y) with complex single-tract Crohn's disease perianal fistula who have failed conventional therapy were included in this study. INTERVENTION: Autologous adipose-derived mesenchymal stem cells were isolated, ex vivo culture expanded, and seeded onto a commercially available bioabsorbable fistula plug. Six weeks later, patients returned to the operating room for removal of the seton and placement of the stem cell-loaded plug. MAIN OUTCOME MEASURES: Patients were followed up for a total of 8 visits through 12 months. Safety was the primary end point; clinical healing and MRI response were secondary end points. RESULTS: Twenty patients (12 females; mean age 36 y) were treated with the stem cell–loaded plug. Of the 20 patients enrolled, 3 were not included in the 12-month analysis because of study withdrawal. Through 12 months, no patient experienced a serious adverse event related to the stem cell–loaded plug. Four patients experienced 7 serious adverse events and 12 patients experienced 22 adverse events. Complete clinical healing occurred in 14 of 18 patients at 6 months and 13 of 17 patients at 12 months. MRI response was observed in 12 of 18 patients at 6 months. LIMITATIONS: The main limitations were the small sample size and restrictive inclusion criteria. CONCLUSIONS: A stem cell–loaded plug can safely and effectively deliver cell-based therapy for patients with single-tract fistulizing perianal Crohn's disease. See Video Abstract at http://links.lww.com/DCR/C70 . RESPUESTA DURADERA OBSERVADA EN PACIENTES CON ENFERMEDAD DE CROHN PERIANAL FISTULIZANTE REFRACTARIA MEDIANTE EL USO DE CÉLULAS MADRE MESENQUIMALES AUTÓLOGAS EN UNA MATRIZ DISOLUBLE: RESULTADOS DEL ENSAYO DE FASE I STEM CELL ON MATRIX PLUG: ANTECEDENTES: La enfermedad de Crohn perianal refractaria sigue siendo notoriamente difícil de tratar. Desarrollamos una tecnología novedosa utilizando un tapón de fístula bioabsorbible disponible comercialmente para administrar células madre mesenquimales derivadas de tejido adiposo autólogo. OBJETIVO: Evaluar la seguridad y viabilidad terapéutica en el ensayo finalizado STOMP. DISEÑO: Ensayo clínico prospectivo de fase I de un solo brazo. AJUSTE: Centro médico académico terciario. PACIENTES: Adultos (18-65) con fístula perianal compleja de la enfermedad de Crohn de un solo tracto que han fracasado con la terapia convencional. INTERVENCIÓN: Se aislaron células madre mesenquimales derivadas de tejido adiposo autólogo, se expandieron en cultivo ex vivo y se sembraron en un tapón de fístula bioabsorbible disponible comercialmente. Seis semanas después, los pacientes regresaron al quirófano para retirar el setón y colocar el tapón cargado de células madre. PRINCIPALES MEDIDAS DE RESULTADO: Los pacientes fueron seguidos durante un total de 8 visitas durante 12 meses. La seguridad fue el criterio principal de valoración; la curación clínica y la respuesta a la resonancia magnética fueron criterios de valoración secundarios. RESULTADOS: Veinte pacientes (12 mujeres, edad media 36 años) fueron tratados con el tapón cargado de células madre. De los 20 pacientes inscritos, tres no se incluyeron en el análisis de 12 meses porque se retiraron del estudio. A lo largo de 12 meses, ningún paciente experimentó un evento adverso grave relacionado con el tapón cargado de células madre. Cuatro pacientes experimentaron 7 eventos adversos graves y 12 pacientes experimentaron 22 eventos adversos. La curación clínica completa ocurrió en 14 de 18 pacientes a los 6 meses y en 13 de 17 pacientes a los 12 meses. La respuesta a la resonancia magnética se observó en 12 de 18 pacientes a los 6 meses. LIMITACIONES: Las principales limitaciones son el tamaño pequeño de la muestra y los criterios de inclusión restrictivos. CONCLUSIONES: Un tapón cargado de células madre se puede administrar de manera segura y efectiva, una terapia basada en células para pacientes con enfermedad de Crohn perianal fistulizante de un solo tracto. Consule Video Resumen en http://links.lww.com/DCR/C70 . (Traducción— Dr. Yesenia Rojas-Khalil )